Eighteenth-Century Russia. - Chrissidis, Nikolaos (2008)
Worked on a book and wrote and presented several paper on eighteenth century Russia.
Keywords: dept.his; faculty_collection; sabbatical_report

Revolution and Union: The American Dilemma 1763-1877 - Gerber, Richard A. (Cengage Learning, 2008)
Keywords: History; Textbooks; United States; dept.his; faculty_collection

The Civil Rights Act of 1875: A Reexamination - Gerber, Richard A.; Friedlander, Alan (Transactions of the Connecticut Academy of Arts and Sciences ; v. 60, p. 1-150, 2008)
Keywords: Civil rights; History; History; African Americans; United States; dept.his; faculty_collection

Reconstructing meaning in Deuteronomy 22:5: Gender, society, and transvestitism in Israel and the ancient Near East - Vedeler, H.T. (Journal of Biblical Literature, 2008)
Keywords: dept.his

Is one world enough for all of us?: Thoughts on globalization - Paddock, Troy R. E. (Dangers in the incommensurability of globalization: socio-political volatilities, 2008)
Keywords: dept.his

The Missouri Controversy and Sectionalism - Forbes, Robert P. (Congress and the Emergence of Sectionalism: From the Missouri Compromise to the Age of Jackson, 2008)
In 1815 the United States was a proud and confident nation. Its second war with England had come to a successful conclusion, and Americans seemed united as never before. The collapse of the Federalist party left the Jeffersonian Republicans in control of virtually all important governmental offices. This period of harmony—what historians once called the Era of Good Feeling—was not illusory, but it was far from stable. One-party government could not persist for long in a vibrant democracy full of ambitious politicians, and sectional harmony was possible only as long as no one addressed the hard issues: slavery, race, western expansion, and economic development.Congress and the Emergence of Sectionalism: From the Missouri Compromise to the Age of Jackson inaugurates a new series for the United States Capitol Historical Society, one that will focus on issues that led to the secession crisis and the Civil War. This first volume examines controversies surrounding sectionalism and the rise of Jacksonian Democracy, placing these sources of conflict in the context of congressional action in the 1820s and 1830s. The essays in this volume consider the plight of American Indians, sectional strife over banking and commerce, emerging issues involving slavery, and the very nature of American democracy.“It is to be regretted that the rich and powerful too often bend the acts of government to their selfish purposes…. There are no necessary evils in government. Its evils exist only in its abuses. If it would confine itself to equal protection, and, as Heaven does its rains, shower its favors alike on the high and the low, the rich and the poor, it would be an unqualified blessing. In the act before me there seems to be a wide and unnecessary departure from these just principles.”—Andrew Jackson, Veto Message Regarding the Bank of the United States, July 10, 1832“I consider, then, the power to annul a law of the United States, assumed by one State, incompatible with the existence of the Union, contradicted expressly by the letter of the Constitution, unauthorized by its spirit, inconsistent with every principle on which it was founded, and destructive of the great object for which it was formed.”—Andrew Jackson, Proclamation Regarding Nullification to the People of South Carolina, December 10, 1832
Keywords: dept.his